Proliferative activity of bone marrow cells of rats under the influence of biologically active substances of a medical leech - R. F. Aminov; A. K. Frolov (Regulatory Mechanisms in Biosystems, 2017)
Hirudotherapy has been used in medicine since time immemorial. The advantage of this type of treatment is that the bite of a leech has a restorative effect on the entire body. The leech bites the skin and injects into the patient’s blood biologically active substances that activate blood microcirculation and promote immunity. The saliva of the leech contains more than 100 substances that contribute to the spectrum of therapeutic effects. But there are no studies on the effect of hirudotherapy on the proliferation of bone marrow cells, which is ontogenetically primary in the development of myeloid and lymphoid tissues. Therefore, it is important to study the mitotic activity of bone marrow of rats at the early stages of postembryonic development against the background of influence by the leech. Female nonlinear rats, two weeks before and two weeks after mating with males, were presented each week to one hungry medical leech weighing 400 mg. The females were examined after feeding their offspring and their offspring were likewise examined on day 1, 15, 30, 45, 60 of the experiment. The animals were kept in vivarium conditions on a standard diet in individual cages. All animals were decapitated under ether anesthesia and the number of leukocytes, the leukocyte blood count, the number of erythrocytes, hemoglobin, and the color index were examined. After that, the femurs were quickly removed and the adjacent muscles separated with a sterile gauze. We cut the epiphyses and cut along the bone. Bone marrow from the femur was flushed with a warm (37 °C) hypotonic 0.9% sodium citrate solution into a sterile centrifuge tube using a Pasteur pipette. The resulting cell suspension was incubated in a hypotonic solution for 10 minutes at 37 °C. The resulting suspension was centrifuged for 5 minutes at 1000 rpm leaving only a small residue of sediment in the test tube. The cells were fixed in methyl alcohol with glacial acetic acid (three parts methyl alcohol and one part acetic acid). 3,000 cells were analyzed, among which we determined those that are in mitosis, and expressed their share. As a result of our studies, the immunomodulating effect of the saliva of the medical leech was revealed, which manifested itself in an increase in the proliferative activity of bone marrow cells, which led to an increase in the number of red blood cells, increased hemoglobin and increase in the number of leukocytes. The color index and the leukocyte blood count were within the normal limits.